The Relationship between Attitude and Early Detection Behavior of Cervical Cancer in the Working Area of the Pakem Health Center - Siti Rukmana; Yaviza Puspitasari (International Journal of Medicine and Health, 2025)
Cervical cancer is a malignant tumor that grows in the cervix caused by infection with the Human Papilloma Virus, acquired through sexual intercourse. Indonesia ranks 8th in the highest incidence of cancer in Southeast Asia, the highest prevalence of cancer is Yogyakarta Province where Sleman Regency ranks the highest IVA positive at 2.5% and Halis IVA at the Pakem Health Center is suspected of cervical cancer reaching 13 out of 22 positive IVA results. This achievement is still very low, because there is still low public awareness to carry out early detection of cervical cancer. To determine the relationship between attitude and behavior for early detection of cervical cancer. Quantitative research with a Case Control approach. A sample of 160 women with a proportional sampling technique. Data collection was in the form of filling out questionnaires online using Google Forms with chi square test data analysis and logistic regression. There was a relationship between positive attitude p-value=0.017 and OR of 3.462, women aged >35 years p- value=0.038, multipara parity p-value=0.007, with early detection behavior of cervical cancer. Parity provided a great chance of 7,038 times that women performed early detection behaviors of cervical cancer (CT 95%= 0.187-264,350). To improve early detection examinations, health workers can design health education and promotion models, increase educational socialization to cadres, the public and the community continuously and sustainably.